Respuesta :

Given that:

[{1(1/5)−(2/5)⋅(−3/4)3}]÷(−9)

= [{(5+1)/5 - (2/5).(-3/4)3}]÷(-9)

= [{(6/5) - (2/5).(-3/4)3}]÷(-9)

= [{(6/5) - (2/5).(-3/4)3}]÷(-9)

= [{(6/5) - (2/5).(-3*3)/4}]÷(-9)

= [{(6/5) - (2/5) . (-9/4)}]÷(-9)

= [{(6/5) - (2/5) × (-9/4)}]÷(-9)

= [{{6/5) - {{2*(-9)}/{5*4}]}]÷(-9)

= [{(6/5) - {-9/(5*2)}}]÷(-9)

= [{(6/5) - (-9/10)}]÷(-9)

Take the LCM of 5 & 10 is 10.

= [{(6*2 + 9*1)/10}]÷(-9)

= [{(12+9)/10}]÷(-9)

= [{-(21/10)}]÷(-9)

= -(21/10) ÷ (-9)/1

= -(21/10) × (1/9)

= {(-21*1)/(10*9)]

= {-21/90)

= {(-21÷3)/(90÷3)}

= -9/30

= {(-9÷3)/(30÷3)}

= (-3/10) = -3/10 Ans.